Examining the underlying principles that guide the design of E-Assessment in Higher Education - Abrahams, Yulene Rulene (University of the Witwatersrand, Johannesburg, 2024)
This qualitative research study explores the values and perspectives of lecturers regarding contemporary e-assessment practices in a South African context. The research addresses a notable gap in the literature concerning the values and principles guiding e-assessment in the specific context of South African higher education. The overarching aim is to deepen and expand existing assessment principles to better align with the demands of contemporary e-assessment. Employing online interviews with five participants, the study utilizes Sadler’s theory of formative assessment as the theoretical framework to analyze the data. The key findings reveal five essential principles guiding e-assessment: Authenticity, Deepening Engagement, Adaptation, Inclusivity, and Credibility. The study's key findings underscore the importance of reevaluating and enhancing existing assessment principles to meet the evolving landscape of digital education, particularly in South Africa.
A research report submitted in fulfillment of the requirements for the Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; e-assessment practices; Higher Education; SDG-4: Quality education